Study the Level of Inclusion in Disaster Risk Reduction for Inclusive Elementary School in Indonesia - Hayati, Nisa Ageng; Nurhayati, Chichi Elsa; Idris, Aceng Fahmi; Lestari, Triana (PGSD Universitas Muria Kudus, 2024)
This research aims to explain how disaster risk reduction in elementary schools can be implemented inclusively and to comprehensively understand research trends regarding DRR in inclusive elementary schools in Indonesia in 2013-2023. The research was conducted using bibliometric methods based on the 2013-2023 Google Scholar database. Data collection is supported using the Publish or Perish (PoP) application. We also use VOSviewer as a data visualization tool capable of creating meshes from processed data sets. From this search, 999 articles were found with the keywords inclusive, disaster risk reduction, elementary schools, and Indonesia. Found 11 terms based on network visualization which were grouped into 2 clusters. The term inclusive school appears 4 times and the term disaster risk reduction appears 14 times. Based on the research results, efforts are needed to be made through inclusive education programs in elementary schools that are in accordance with the need to reduce disaster risk in schools both before, during and after disasters.